Cholera on high alert - Yamna Waseem; Tarin, Taha Ahmed; Kumar, Anish (Journal of the Pakistan Medical Association, 2022)
Madam, cholera is an acute bacterial infection of the intestine caused by the Vibrio cholera bacteria. Cholera spreads via the faecal-oral route and causes severe diarrhoeal infection. According to the World Health Organization, every year, three million to five million cases of cholera appear; among them 100,000-200,000 deaths occur globally [1]. The disease has been associated with seven pandemics in the past. The first pandemic of cholera occurred in 1817 [2]. In the 19th century, an outbreak of cholera in the Ganges delta, in India, led to the spread of cholera across the world. Six subsequent pandemics of cholera have since then killed millions of people. Later, in 1961, 1971, and 1991, outbreaks occurred in South Asia, Africa, and America respectively. Cholera is now endemic in most Southeast Asian countries, including Pakistan. —Continue